2011
DOI: 10.1186/1742-4690-8-s1-a184
|View full text |Cite
|
Sign up to set email alerts
|

APH-2 and Tax expression are correlated with a HTLV-2 proviral load but not with lymphocytosis

Abstract: International audiencen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Douceron et al . observed that expression of HTLV-2 APH-2 and Tax are correlated with HTLV-2 proviral load, but not with lymphocytosis; consistent with this, APH2 (contrary to HBZ of HTLV-1) did not promote cell proliferation in vitro [ 105 ]. The nuclear localization of complementary strand transcripts of both HTLV-1 and HTLV-2 [ 95 ] might favour viral persistence by reducing translation and exposure of the infected cell to the CTL response while allowing function as a non-coding transcripts.…”
Section: Virologymentioning
confidence: 74%
“…Douceron et al . observed that expression of HTLV-2 APH-2 and Tax are correlated with HTLV-2 proviral load, but not with lymphocytosis; consistent with this, APH2 (contrary to HBZ of HTLV-1) did not promote cell proliferation in vitro [ 105 ]. The nuclear localization of complementary strand transcripts of both HTLV-1 and HTLV-2 [ 95 ] might favour viral persistence by reducing translation and exposure of the infected cell to the CTL response while allowing function as a non-coding transcripts.…”
Section: Virologymentioning
confidence: 74%